2022
DOI: 10.1038/s41467-022-31296-2
|View full text |Cite
|
Sign up to set email alerts
|

A practical fluorosulfonylating platform via photocatalytic imidazolium-based SO2F radical reagent

Abstract: Sulfonyl fluorides are key components in the fields of chemical biology, materials science and drug discovery. In this line, the highly active SO2F radical has been employed for the construction of sulfonyl fluorides, but the utilization of gaseous ClSO2F as radical precursor is limited due to the tedious and hazardous preparation. Meanwhile, the synthesis of sulfonyl fluorides from inert SO2F2 gas through a fluorosulfonyl radical (·SO2F) process has met with inevitable difficulties due to the high homolytic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…We further concluded that switching the reactivity mode by introducing a hydrogen atom donor could enable the rapid synthesis of the aliphatic sulfonyl fluorides. Notably, while our studies were underway, Wang and co-workers as well as Song and Liao and co-workers reported the hydro-fluorosulfonylation of alkenes by utilization of benzimidazolium salts as sulfonyl fluoride radical precursors and cyclohexadiene as hydrogen source by photoredox catalysis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We further concluded that switching the reactivity mode by introducing a hydrogen atom donor could enable the rapid synthesis of the aliphatic sulfonyl fluorides. Notably, while our studies were underway, Wang and co-workers as well as Song and Liao and co-workers reported the hydro-fluorosulfonylation of alkenes by utilization of benzimidazolium salts as sulfonyl fluoride radical precursors and cyclohexadiene as hydrogen source by photoredox catalysis.…”
Section: Introductionmentioning
confidence: 97%
“…Liao and co-workers applied sulfuryl chloride fluoride under mild photoredox conditions to furnish alkenyl sulfonyl fluorides from alkenes, while alkynes underwent chloro-fluorosulfonylation . Very recently, benzimidazolium-based reagents (Figure A) were simultaneously uncovered by Wang and Liao , group independently to serve as sulfonyl fluoride radical precursors by photoredox catalysis, enabling the synthesis of alkenyl sulfonyl fluorides and β-alkoxy sulfonyl fluorides, among other functionalities. Weng and co-workers formed carbon-centered radicals by proton-coupled electron transfer (PCET) to amides and intramolecular 5- exo -trig cyclization with alkenes or by energy transfer (EnT)-mediated decarboxylation of oxime esters .…”
Section: Introductionmentioning
confidence: 99%
“… 27 Most recently, Liao and Wang groups reported that fluorosulfuryl imidazolium salt could produce SO 2 F radical and enabled fluorosulfonylation of olefins. 28 …”
mentioning
confidence: 99%
“…At the same time, Wang and co-workers reported the same air-and bench-stable benzoimidazolium fluorosulfonate reagent from their previous work on the chemistry of imidazolium sulfonate cationic salts, 16 which successfully applied to the radical fluorosulfonylation of unsaturated hydrocarbons (Scheme 6). 17 Under suitable optimized photocatalytic con- ditions, this redox-active fluorosulfonyl radical precursor could react with various alkenes smoothly, providing alkenyl sulfonyl fluoride, alkylsulfonyl fluoride, and migratory fluorosulfonylat-ing products in good yields with high stereoselectivity. This operationally simple protocol enabled the efficient introduction of the FSO 2 group into a wide range of complex molecules derived from natural products and drugs.…”
mentioning
confidence: 99%